Thick-film photoimageable and laser-shaped arms for thermoelectric microgenerators - Markowski, Piotr (Microelectronics international, 2011)
Purpose - The purpose of this paper is to investigate the possible application of thick-film, metal-based thermocouples to microsystems power supply. The subject of matter was development of the procedure of thick-film thermopile miniaturisation.Design methodology approach - The aptitude of four photoimageable inks (based on silver or silver-palladium) to fabrication of miniaturised thermocouples' arms was investigated. The object of interest was their compatibility with different kinds of low temperature cofired ceramic (LTCC) substrates, maximum resolution, shrinkage and electrical resistivity. Usage of the laser shaping technique to fabrication of narrow thermocouples' arms was also subject of matter. After tests and processes optimization both techniques were combined to fabricate the thick-film Ag Ni microthermopile.Findings - Most of investigated inks were compatible with all tested LTCC tapes - fired as well as unfired (green tapes). Photoimageable inks technique can be successfully used for thermocouples' arms miniaturization. 40 μm 40 μm line spaces resolution can be easily achieved. Combining this technique with laser shaping enabled microthermopile fabrication. It consisted of 42 Ag (photoimageable) Ni (laser shaped) thermocouples. Arms width was 40 μm and 225 μm (Ag- and Ni-arm, respectively), spaces between them - 65 μm. Overall, width of single thermocouple was smaller than 0.4 mm.Practical implications - Fabrication of microthermopile consisting of several hundreds of thick-film thermocouples will be possible if described procedure is applied. Such microgenerator will generate output power sufficient to supply some microsystems or microelectronic circuits.Originality value - The properties of four photoimageable inks were investigated as well as their compatibility with five different LTCC substrates (fired and unfired). Procedure of thick-film microthermopile fabrication using photoimageable inks technique combined with laser shaping was proposed for the first time.